2001
DOI: 10.1109/77.920132
|View full text |Cite
|
Sign up to set email alerts
|

Fault current tests of a 5-m HTS cable

Abstract: Abstract-The first industrial demonstration of a threephase high-temperature superconducting transmission power cable at the Southwire manufacturing complex is in progress. One crucial issue during operation of the 30-m HTS cables is whether they could survive the fault current (which can be over an order of magnitude higher than the operating current) in the event of a short-circuit fault and how HTS cables and the cryogenic system would respond. Simulated fault-current tests were performed at ORNL on a 5-m c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…There is widespread experience with signals containing a false component that, in spite of being in phase with the cable current, does not have anything to do with the true loss. Sometimes it is preferred to utilize the voltage drop as measured between the current terminations, containing the loss signal from superconductor on a large resistive background [5][6][7][8]. In this case, the results are obtained after subtracting the loss in current termination from the total measured loss.…”
Section: Introductionmentioning
confidence: 99%
“…There is widespread experience with signals containing a false component that, in spite of being in phase with the cable current, does not have anything to do with the true loss. Sometimes it is preferred to utilize the voltage drop as measured between the current terminations, containing the loss signal from superconductor on a large resistive background [5][6][7][8]. In this case, the results are obtained after subtracting the loss in current termination from the total measured loss.…”
Section: Introductionmentioning
confidence: 99%
“…Previous tests on a different 5-m cable using a nonalloyed silver BSSCO-2223 tape without a splice showed that for an overcurrent of 10 kA the cable resistance went to 0.16 mΩ and did not increase much during the pulse. 9 The alloy sheath of the HTS tapes in the splice cable has higher resistance and produces more heat in overcurrents.…”
Section: The DC V-i Curves and Overcurrent Testsmentioning
confidence: 99%
“…They have found out that the level of the tape degradation is not dependent on the initial value of the critical current, but on the peak value of the reached temperature. Overcurrent testing of superconducting tapes and cables was mainly performed by means of a constant current source for investigating the magnet or cable stability [4][5][6].…”
Section: Introductionmentioning
confidence: 99%